Complete absence of external genitalia in limb-body wall complex: two cases. Issue 5 (May 1988) - Litwin, A; Merlob, P; Grunebaum, M
Abstract : Two neonates with limb-body wall complex (LBWC) and complete absence of the external genitalia are presented. Our patients are the sixth and seventh cases of complete absence of the external genitalia recorded in English publications and the first two cases associated with LBWC. The incidence of complete absence of the external genitalia in our newborn population during a period of 12 years (1975 to 1986) was one case per 13 420 births.